Bump Morphology of the CMAGIC Diagram - L. Aldoroty; L. Wang; P. Hoeflich; J. Yang; N. Suntzeff; G. Aldering; P. Antilogus; C. Aragon; S. Bailey; C. Baltay; S. Bongard; K. Boone; et al. (The Astrophysical Journal, 2023)
We apply the color–magnitude intercept calibration method (CMAGIC) to the Nearby Supernova Factory SNe Ia spectrophotometric data set. The currently existing CMAGIC parameters are the slope and intercept of a straight line fit to the linear region in the color–magnitude diagram, which occurs over a span of approximately 30 days after maximum brightness. We define a new parameter, ω _XY , the size of the “bump” feature near maximum brightness for arbitrary filters X and Y . We find a significant correlation between the slope of the linear region, β _XY , in the CMAGIC diagram and ω _XY . These results may be used to our advantage, as they are less affected by extinction than parameters defined as a function of time. Additionally, ω _XY is computed independently of templates. We find that current empirical templates are successful at reproducing the features described in this work, particularly SALT3, which correctly exhibits the negative correlation between slope and “bump” size seen in our data. In 1D simulations, we show that the correlation between the size of the “bump” feature and β _XY can be understood as a result of chemical mixing due to large-scale Rayleigh–Taylor instabilities.